Educação ambiental como instrumento de ensino sobre mudanças climáticas por meio de jogos ambientais - Pimenta, Daniela (Universidade Federal de São Carlos, 2025)
The present study consisted in practical analysis of the use by educational games as a tool for environmental education. The research was carried out with fourth-grade students from the municipal school system in Votorantim/SP. For this purpose, an environmental game on climate change was developed, addressing topics such as greenhouse effect, causes and consequences of climate change, and possible mitigation strategies. In addition to playful activity, the students answered a written questionnaire, allowing for evaluation of their understanding about topics presented. The results showed significant improvements in learning, confirming the effectiveness of educational games as a resource to promote awareness and the development of values related to sustainability and fight against climate change.
Environmental education as a teaching tool on climate change through environmental games
Keywords: Educação Ambiental; Mudanças Climáticas; Jogo Ambiental; Environmental Education; Climate Changes; Environmental Game; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS; 13. Ação contra a Mudança Global do Clima; 11. Cidades e Comunidades Sustentáveis